Assessment of Gnetum gnemon Fruit Extract as a Natural Sunscreen Cream Formulation, Skin-Brightening, and Anti-Aging Agent - Rifki Fadhilatil Aqli; Everest Azahra Wibisono; Royan Mahmud Musthofa; Hamzah Fansuri (LPPM Universitas Abdurrab, 2026)
The use of sunscreen is an essential measure to protect the skin from the harmful effects of ultraviolet (UV) radiation. Along with the increasing interest in natural ingredients, melinjo fruit (Gnetum gnemon L.) has the potential to be developed as an active ingredient source in skincare products. Melinjo is known to contain bioactive compounds such as phenols, flavonoids, and stilbenoids, which exhibit photoprotective activity and high antioxidant properties, enabling the absorption of UV radiation and the prevention of free radical formation that causes dull skin and premature aging. This study aims to explore the potential of melinjo fruit extract as a natural-based active ingredient for sunscreen, brightening, and anti-aging applications. The research methods included extraction of melinjo fruit using the maceration technique, formulation of the optimal cream containing 59.42% (w/v) olive oil and 6% (w/v) melinjo extract, and evaluation through Sun Protection Factor (SPF), tyrosinase inhibition, antioxidant activity, pH, and skin irritation tests. The results showed that the formulated sunscreen cream exhibited an SPF value of 56.12, classified as ultra protection. In addition, melinjo extract demonstrated tyrosinase inhibition activity and anti-aging potential with an IC50 value of 39.87 ppm. The irritation test indicated that the product was safe and did not cause skin irritation